PERBANDINGAN KEMAMPUAN AFEKTIF SISWA KELAS XI SMAN 1 SULIKI ANTARA PENGGUNAAN HANDOUT DILENGKAPI PETA KONSEP DAN PETA PIKIRAN DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) - Asti febrina Asti (Perspektif Pendidikan dan Keguruan, 2021)
Based on the observations made at SMAN 1 Suliki on August 20, 2015, the reality is that in the learning process, attention and negative student activities in the classroom are still many such as, drowsiness during learning, and lack of interaction between students and teachers during the teaching and learning process. Students also lack interact with each other, in conducting group discussions. Highly capable students are still unable to work with low-skilled students. The learning resources used by teachers in the field of study are still package books, so that makes students only control package books in learning. The other learning resources provided in schools are LKS, but the delivery of materials in this LKS is still not colored. Every time they start learning, students still forget to bring a package book. Therefore, learning ppenelitian becomes less effective because of the lack of teaching materials used by teachers and learning methods that are still not appropriately used by teachers. Then the creation of mind map handouts and concept maps with STAD learning models is the solution.This type of research is quasi experimental research. The sampling technique used is purposive sampling technique by assigning experiment class I and class II experiment in drawn. So that obtained the selected sample class XI IPA5 and XI IPA6. The research instrument used is the instrument used for the assessment of the affective aspects of students is the assessment sheet of affective aspects. This assessment sheet aims to assess students' attitudes and behaviors during the learning process. The assessment sheet contains the observed aspects of students' attitudes and behaviors. Based on the results of the research conducted showed that in the affective realm by using handouts of mind maps and concept maps in cooperative learning models STAD is 93.16 (class I experiment) category is very good, and 72.25 (experiment II) with good category. In the first class of experiments have better affective competence than the second class of experiments.